The Quotation of Jer. 31.15 in Mt. 2.18 within Christological Patterning of Matthew’s Nativity According to the Joseph Story - Akagi, Kai 1987- (2023)
The quotation of Jer. 31:15 in Mt. 2:18 has proven to be an interpretive puzzle through its otherwise unattested form of Jer. 31:15 and the seemingly unclear relationship of the quotation to its context in Matthew. Marten J. J. Menken has argued that Matthew quotes a text of Jer. 31:15 that is combined with Gen. 37:35 but that this composite citation does not have interpretive significance for Matthew. When viewed in the context of a series of lexical and thematic parallels between Matthew’s nativity and the Joseph story, it may be understood, however, as a composite citation occurring in the composition of Matthew for christological purposes. These may include presenting Jesus as participating in his people’s history, implicit response to expectations of a Josephite messiah, and portraying Jesus as saving his people by giving them life. Such use in Matthew of the Joseph story through Jeremiah suggests further need for the study of multilayered use of texts in the New Testament and related literature.